Abnormal Sense of Agency in Patients with Schizophrenia: Evidence from Bimanual Coupling Paradigm - Garbarini, Francesca; Mastropasqua, Angela; Sigaudo, Monica; Rabuffetti, Marco; Piedimonte, Alessandro; Pia, Lorenzo; Rocca, Paola (Frontiers in Behavioral Neuroscience, 2016)
A fruitful approach to the understanding the human awareness of action is the study of those pathologies in which some aspects of it are altered. Previous evidences showed that patients with schizophrenia tend to attribute someone else’ actions to their own, as internally, rather than externally, generated. Here, we asked whether schizophrenics have an “excessive” sense of agency, while observing others’ movements. We took advantage from the circles-lines task, known to show bimanual interferences. Twenty schizophrenics and twenty age-matched healthy controls were administered a) the bimanual version of the task: drawing lines with one hand and circles with the other; and b) a modified version: drawing lines while observing the examiner drawing circles. In the bimanual version, patients and controls showed a comparable interference effect. In the observation version, schizophrenics, compared to controls, showed a significantly greater interference effect of the examiners’ hand drawing circles on the own hand drawing lines. This effect was significantly correlated to the strength of the positive symptoms (hallucinations and delusions) and to the alteration of the sense of agency, reported during the task. These findings suggest that an altered sense of agency, as shown by schizophrenics, can induce objective consequences on the motor system.